Effective marketing of high-rise luxury condominiums in a middle-income country like Sri Lanka. Issue 1 (6th October 2015) - Anthonisz, Stephan; Perry, Chad
Abstract : Purpose: The purpose of this paper is to develop an effective process to market high-rise luxury condominiums in a middle-income country in Asia like Sri Lanka, based on empirical evidence. Design/methodology/approach: The case research methodology used to address the four research issues used multiple sources of data. In stage 1, qualitative data were collected in interviews with managers and salespersons of six condominium developments that ranged from successful to failure. In stage 2, quantitative data were collected in a survey of the buyers of the six cases. Findings: The authors contributions to knowledge include the first evidence-based findings about what influences the success and failure of high-rise luxury condominium developments in a country like Sri Lanka. In addition, a comprehensive marketing model of an effective marketing process is developed for forward-thinking professionals in the field to use to successfully market their luxury high-rise condominiums projects in the future. Practical implications: Detailed steps for successful marketing are outlined, from the Board of Management down to salespersons. Originality/value: This is the first academic research paper to examine the effective marketing of high-rise luxury condominiums in a middle-income country like Sri Lanka.